TINJAUAN HUKUM TERHADAP PERLINDUNGAN KONSUMEN DALAM PENGGUNAAN JASA LAUNDRY MENURUT UNDANG-UNDANG NO. 8 TAHUN 1999 - Hidayani, Sri; Lubis, Anggreni Atmei (GOVERNANCE: Jurnal Ilmiah Kajian Politik Lokal dan Pembangunan, 2023)
Consumer guarantees are getting considerate, considering consumers as services that should be protected. Due to the lack of knowledge and understanding of consumers on their rights as consumers, and business actors who neglect or make mistakes, make the consumer's position lower than the business actor. The laundIn the results of this study found that in the responsibility as a businessman laundry service for losses suffered by consumers is to provide compensation, although not full according to the price of damaged or lost items. The most frequent solution done by the businessman laundry services DI'Wash and consumers is by using the deliberation path because it is more efficient and does not use a lot of funds.